Vehicle Routing 2014
DOI: 10.1137/1.9781611973594.ch10
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 10: Vehicle Routing Problems with Profits

Abstract: The key characteristic of the class of Vehicle Routing Problems with Profits (VRPPs) is that, contrary to what happens for the most classical vehicle routing problems, the set of customers to serve is not given. Therefore, two different decisions have to be taken: (i) which customers to serve, and (ii) how to cluster the customers to be served in different routes (if more than one) and order the visits in each route. In general, a profit is associated with each customer that makes such a customer more or less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 59 publications
0
71
0
Order By: Relevance
“…Much fewer studies can be found on the PTP (Archetti et al 2014). An approximation algorithm for the asymmetric PTP is presented by Nguyen and Nguyen (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Much fewer studies can be found on the PTP (Archetti et al 2014). An approximation algorithm for the asymmetric PTP is presented by Nguyen and Nguyen (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A classification of traveling salesman problems with profits is given in Feillet et al (2005). While in the TOP, the objective is to maximize the total collected profit, other problems, like the prize-collecting VRP, minimize the total traveling cost (Feillet et al 2005;Tang and Wang 2006;Archetti et al 2014). If a carrier can either visit a customer with one of his vehicles or assign the customer to a common carrier, the problem is referred to as VRP with private fleet and common carrier which is investigated by, e.g., Chu (2005), Bolduc et al (2008), Stenger et al (2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because shortening vehicles running distances will promote the efficiency of vehicles and drivers. In addition, the algorithm can improve customers service quality, reduce exhaust emissions, and promote vehicles dispatch efficiency [3]. Consequently, the research of vehicle routing problem, which is a significate topic, has grabbed the scholars' attentions during the past few decades [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the recent years, some issues (e.g., global warming, resource scarcity, traffic congestion and pollution) are causing companies and governments to design logistic systems effectively (Archetti et al, 2014). The VRP is a complex problem in the field of operations research.…”
Section: Introductionmentioning
confidence: 99%